2013
DOI: 10.1111/jcms.12093
|View full text |Cite
|
Sign up to set email alerts
|

Greece in Crisis: Austerity, Populism and the Politics of Blame

Abstract: Within the broader debate on the Greek crisis, the theory of 'populist democracy' postulates that populism is fundamental to the sustenance of the Greek political system and is at the heart of Greece's endemic domestic weaknesses. This article tests this assumption empirically through the use of a sophisticated framing analysis of speeches delivered by the leaders of the five parties in the Greek parliament in the period 2009-11. The findings confirm that populism: (a) is expressed through the narratives of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
110
3
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 160 publications
(128 citation statements)
references
References 15 publications
(20 reference statements)
1
110
3
4
Order By: Relevance
“…Other far right parties have enjoyed electoral success in Greece, for example the Popular Orthodox Rally (LAOS) and Independent Greeks (ANEL). However, these fall within the radical right category (Vasilopoulou and Halikiopoulou 2015) and their support is more consistent with the predictions of existing theories. By contrast, the Golden Dawn falls into the extreme right category.…”
supporting
confidence: 62%
See 3 more Smart Citations
“…Other far right parties have enjoyed electoral success in Greece, for example the Popular Orthodox Rally (LAOS) and Independent Greeks (ANEL). However, these fall within the radical right category (Vasilopoulou and Halikiopoulou 2015) and their support is more consistent with the predictions of existing theories. By contrast, the Golden Dawn falls into the extreme right category.…”
supporting
confidence: 62%
“…The result was the emergence of a new cleavage in Greece, expressed through strong support for anti-systemic and anti-memorandum parties (Dinas and Rori 2013;Vasilopoulou and Halikiopoulou 2013). In other words, the crisis of political representation opened up a space for parties beyond the confines of the system -parties that offered an alternative vision of representation and more broadly an alternative solution to the crisis -such as the Golden Dawn.…”
Section: The Rise Of the Extreme Right: A Crisis Of Democratic Represmentioning
confidence: 99%
See 2 more Smart Citations
“…the pure people versus the corrupt elite, is less helpful in the case of Greece. This is because research has shown that Greece is a populist democracy, with populism observed across the party system rather than by specific actors (Pappas, 2013;Vasilopoulou et al, 2014). 1 Drawing upon theories of party competition and Euroscepticism (De Vries and Hobolt, 2012;Helbling et al, 2010;Sitter, 2001;Taggart, 1998;van de Wardt et al, 2014;Vasilopoulou, 2018;Whitefield and Rohrschneider, 2015), the article hypothesizes that in times of crisis (1) mainstream parties will maintain their positive EU position, but are likely to increase EU issue salience; (2) challenger parties will emphasize their extreme positions on the EU, but the prospect of government participation is likely to result in them softening their Eurosceptic agenda; and (3) frames related to the specific nature of the crisis are likely to predominate across the party system.…”
Section: Introductionmentioning
confidence: 99%